Kontigensi Perilaku Birokrasi Pemda: Reviu Hasil Penelitian Disertasi Almarhum Dr. Kadjatmiko, M.Soc.Sc. - Surya Dharma; Simatupang Patar (Jurnal Ilmiah Ilmu Administrasi Publik, 2010)
Each organization, include the organization of kabupaten and kota governments in Indonesia unavoidably needs bureaucracy. The behaviour of bureaucracy is not independent, but attributable to and affected by other factors. The result of the research is the behaviour of the bureaucracy of governments in kabupatens and kotas was marked with the strengthening of the characteristics of professional bureaucratic behaviour in the form of being open, adaptive and appreciative; form of activities that are based on formal and informal relation; nature of common activities bound by shared vision and mission of providing public services, etc. The existing local government’s leadership, organizational structure and learning organization are perceived as the main driver in building trust among colleagues that leads to organizational change. Therefore, these factors does have significant effect on bureaucracy.